Dominance in Habitat Preference and Diurnal Explorative Behavior of the Weakly Electric Fish Apteronotus leptorhynchus - Raab, Till; Linhart, Laura; Wurm, Anna; Benda, Jan (Frontiers in Integrative Neuroscience, 2019)
Electrocommunication and -localization behaviors of weakly electric fish have been studied extensively in the lab, mostly by means of short-term observations on constrained fish. Far less is known about their behaviors in more natural-like settings, where fish are less constrained in space and time. We tracked individual fish in a population of fourteen brown ghost knifefish (Apteronotus leptorhynchus) housed in a large 2  indoor tank based on their electric organ discharges (EOD). The tank contained four different natural-like microhabitats (gravel, plants, isolated stones, stacked stones). In particular during the day individual fish showed preferences for specific habitat which provided appropriate shelter. Male fish with higher EOD frequencies spent more time in their preferred habitat during the day, moved more often between habitats during the night, and less often during the day in comparison to low-frequency males. Our data thus revealed a link between dominance indicated by higher EOD frequency, territoriality, and a more explorative personality in male A. leptorhynchus. In females, movement activity during both day and night correlated positively with EOD frequency. In the night, fish of either sex moved to another habitat after about 6 seconds on average. During the day, the average transition time was also very short at about 20 seconds. However, these activity phases were interrupted by phases of inactivity that lasted on average about 20 minutes during the day, but only 3 minutes in the night. The individual preference for daytime retreat sites did not reflect the frequent explorative movements at night.